Understanding Project Complexity Influences on Complex IT Project Success - Fajar Rizky; Teguh Raharjo; Ni Wayan Trisnawaty (Universitas Airlangga, 2026)
Background: The increasing complexity of IT projects in government organizations poses significant challenges for civil servants managing them. Previous studies suggest that complexity encompassing organizational, technological, and administrative dimensions can significantly affect IT project success. However, the specific impact of each complexity type on project innovation and success in the public sector, particularly in Indonesia, remains underexplored. Objective: The study investigates how project complexity affects the success of IT projects in Indonesia's public sector, focusing on civil servant's perspectives. The need arises from challenges in managing complex projects, particularly in organizational, technological, and administrative dimensions. Methods: This quantitative research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data collected from 139 Indonesian civil servants. The survey used a Likert-scale questionnaire to measure the impact of project complexity on IT project success through the lens of project innovation. Results: The study revealed that organizational and technological complexities are crucial in fostering innovation within IT projects, ultimately enhancing their success. The findings indicate that when project teams effectively navigate organizational structures and adapt to technological challenges, they can cultivate an innovative environment that improves project outcomes. Administrative complexity does not significantly influence project innovation, indicating that rigid bureaucratic processes may fail to support creative problem-solving or achieve project objectives. Overall, the study underscores the importance of managing key aspects of project complexity to achieve higher success rates in complex IT projects within Indonesia’s public sector. Conclusion: The study emphasizes managing organizational and technological complexities to enhance innovation and project success in Indonesia’s public sector. The insignificant impact of administrative complexity suggests that rigid bureaucracy may hinder innovation. Future research should explore strategies to simplify administration and improve project management in government institutions. Keywords: Project Complexity, IT Project Success, Civil Servants, Public Sector, PLS-SEM